Media Pembelajaran Berbasis Android Melalui Pendekatan Developmentally Appropriate Practice (DAP) Untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Ardi, Mufakkirul; Nurlan Kusmaedi; Tite Juliantine; Dian Budiana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Students' lack of understanding of the activities and movements in the invasion game material which refers to the learning objectives that are not achieved so that it has an impact on low student learning motivation. This study aims to develop an android-based learning media for elementary school students through the Developmentally Appropriate Practice (DAP) approach. This study is a type of development research (R&D) using the ADDIE development model. Data collection techniques in this study are quantitative data through material validation questionnaires, learning design validation, learning media validation, and determination of validation classification by experts based on the number of answer scores. Data are analyzed and processed descriptively into interval data using a Likert scale. The results obtained are in the form of an android-based learning media through the Developmentally Appropriate Practice (DAP) approach, which can be used as a learning media on material the invasion game of the fourth grade PJOK elementary school invasion game, the results of the feasibility assessment based on material validation with a score of 62 or 88.57%, a learning design validation score of 52 or 86.67%, and a learning media validation score of 69 or 92%. As well as the teacher's assessment as a practitioner of 91.02%. The effectiveness test results showed differences in student learning motivation before and after the implementation of the Android-based learning media through DAP. It was concluded that the android-based learning media that had been developed was declared effective for use in PJOK learning of invansion game material in Elementary Schools. The implication of this research is that the Android-based learning media through this approach can be used as learning media in PJOK learning activities.